The effect of chestnut wood flour size on the mechanical properties of vinyl ester composites - DEMİRER, HALİL; KARTAL, İLYAS (ICE PUBLISHING, 2020)
Green composites are a special class of composites in which at least one of the components is obtained from natural resources. They are an alternative to traditional composites because of their useful properties such as biodegradability, low cost, easy processability, sound insulation and recycling. Green composites, which emerge as environmentally friendly polymeric composite materials, offer techno-economic advantages in commercial and engineering applications and are among the widely dealt subjects due to the very high demand from the global market. The aim of this study is to investigate the effect of chestnut wood flour size on the mechanical properties of chestnut-wood-flour-filled vinyl ester composites. With this aim, composite specimens were produced by using vinyl ester polymer as the matrix material and chestnut wood flour in three different sizes (0-150, 150-315 and 315-400 mm) as the natural filler. In each size combination, four different matrix/filler ratios (5, 10, 15 and 20% by weight) were adopted. These mixtures were then poured into Teflon moulds to produce the test specimens. Izod impact, three-point bending, hardness and tensile strength tests were performed on the composite specimens. In addition, morphological investigations were performed on the fractured surfaces of the specimens by using scanning electron microscopy. It is concluded that composites with a small-sized chestnut wood flour as the filler have superior properties for composite applications.
Keywords: composite materials; mechanical properties; morphology; TRIBOLOGICAL BEHAVIOR; FIBER; CARBON; GLASS; SAWDUST; POLYMER